Under the Empire of Technique: Instrumental Reason and the Rejection of Politics in the Formation of the Central Bank of Brazil - Cornélio dos Santos e Carvalho, Ricardo Vinicius; Paes de Paula, Ana Paula (Organizações & Sociedade, 2023)
Using the critique of instrumental rationality, based on Weber, Habermas and Arendt, we analyze, through interviews of the leaders involved in the creation of the Central Bank of Brazil (BCB), the tension between politics and technique in its formation as a bureaucracy. This oral history research was based on interviews conducted by CPDOC/FGV, published in 2019, in 25 volumes of the "Told History of the Central Bank of Brazil Collection," with leaders who participated in the creation of the BCB. As a result, we identified a discourse of rejection of politics in general and aversion to left-wing policies in particular, in addition to the sacredness of technique, giving rise to a technocratic vision of the BCB, an organization that is seen as bureaucratically insulated, but in which only one technique would be possible: the neoclassical liberal economic view. These two dimensions combine to establish a position of subjection of politics to technique in which even democracy can be sacrificed as an opportunity to implement a certain technical-economic agenda. There are indications, therefore, of an instrumentality of reason in the manifestations analyzed, in pitting technique against politics, which can lead to a process of banalization of evil as criticized by Arendt, especially in seeing regimes of exception in the country as mere opportunities to create the BCB and to implement a liberal-economic agenda. This perspective transforms technique into a political obstacle, including with the rejection of the greatest product of democratic political participation in the country, the 1988 Constitution.